How Did Imam At-Thabari's Interpretation with Tafsir bil Ma'tsur Style Influence Qur'anic Exegesis and Ulama During the Abbasid Dynasty Era? - Lumah, Diana Durrotul; Nasrullah, N; Salsabila, Bilqist Adna; Almaliki, Faruk (QiST: Journal of Quran and Tafseer Studies, 2025)
Tafsir bil ma'tsur is a method of interpreting the Qur'an based on authoritative sources such as the Qur'an, hadith, opinions of companions, and tabi'in. In the Abbasid era, this method developed rapidly along with the increasing attention to the science of interpretation and codification of hadith. Imam At-Thabari was one of the leading figures who lived in the Abbasid era when science developed rapidly. The purpose of this study is to analyze the characteristics of Imam At-Thabari's interpretation in interpreting the Qur'an. This study uses a qualitative descriptive method with a library research approach. The data collection techniques used are documentation techniques and reading techniques. The results of this study indicate that tafsir bil ma'tsur in the Abbasid era experienced more mature methodological developments, especially in the aspects of criticism of sanad and the selection of stronger narrations. The influence of its methodology was very significant in the Abbasid era, which became the main reference for subsequent interpreters and formed the standard in the tradition of interpreting the Qur'an. This study contributes to the understanding of the evolution of tafsir methodology in the golden age of Islam and its relevance to the development of contemporary studies.